Association of respondent psychiatric comorbidity with family history of comorbidity: Results from the National Epidemiologic Survey on Alcohol and Related Conditions-III - Jung, Jeesun (Compr Psychiatry, 2016)
OBJECTIVE: Substance use disorders and major psychiatric disorders are common, highly comorbid with each other, and familial. However, the extent to which comorbidity is itself familial remains unclear. The purpose of this study is to investigate associations between comorbidity among respondents with family history of comorbidity. METHODS: We analyzed data from the National Epidemiologic Survey on Alcohol and Related Conditions-III to study the associations of family history (FH) of comorbidity among alcoholism, drug problems, depression, antisocial behavior, and anxiety disorders in parents and maternal and paternal grandparents with corresponding DSM-5 diagnostic comorbidity among respondents. We utilized multivariable multinomial logistic regression models controlling for age, sex, race, education, family income, marital status, and adverse childhood experiences (ACEs). RESULTS: All comorbid associations of any two disorders with FH were statistically significant; almost all adjusted odds ratios (ORs) for respondent comorbidity in the presence of FH of the parallel comorbidity exceeded 10. ORs involving antisocial behavior in relatives and antisocial personality disorder in respondents were consistently larger than any other pairs of disorders. After further adjustment for ACEs, most patterns of association were similar but the ORs were reduced two to threefold. ACEs may be mediators in relationships between familial and respondent comorbidities. CONCLUSION: Further investigations of relationships among familial comorbidity, ACEs, and respondents’ diagnoses may improve understanding of comorbidity.